Case report: Disseminated mucormycosis misdiagnosed as malignancy developed from allergic bronchopulmonary mycosis caused by Rhizopus microsporus following SARS-CoV-2 infection in a woman - Kong, Chengying; Zong, Laibin; Ji, Shunxian; Liu, Yangxiang; Li, Miaomiao (Frontiers in Medicine, 2024)
Mucormycosis has become more prevalent during the COVID19 pandemic and is associated with a high mortality rate. However, concurrent host allergic reactions, invasive pulmonary mucormycosis, and disseminated mucormycosis are rarely reported. Herein, we describe a case of disseminated mucormycosis initially misdiagnosed as a malignancy that developed from allergic bronchopulmonary mycosis caused by Rhizopus microsporus in a woman with post-SARS-CoV-2 infection. The previously healthy patient presented with a sizeable mass in the right middle lobe and multiple lesions across the lungs, brain, spleen, kidneys, pancreas, and subcutaneous tissue 6 months after SARS-CoV-2 infection, mimicking an extensive metastatic malignancy. Eosinophilia, elevated total plasma immunoglobulin E, and significant eosinophilic lung tissue infiltration were observed. Rhizopus microsporus was isolated from subcutaneous tissue, and hyphae were detected in the lung tissue. Sequential amphotericin B liposomes followed by isavuconazole antifungal therapy combined with systemic corticosteroids improved symptoms, significantly reduced the sizes of pulmonary lesions, and reduced eosinophil count. However, it failed to halt the overall progression of the disease, and the patient died. The absence of asthma-like symptoms and delayed recognition of invasive fungal infection signs contributed to poorer outcomes, highlighting the need for a thorough post-COVID-19 follow-up.